Internet tools in marketing communication - Kaczmarek, Bartłomiej (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
The purpose of this article is to describe internet tools that are used in modern marketing communication. Basic definitions and models are explained within the article. The author of the article described also new trends in marketing, especially connected to development of internet technologies and social or cultural changes. The article refers also to examples of internet tools that helps companies to communicate with their stakeholders.